Numerical simulation of one-dimensional problems of termoelasticity in the presence of heat flux, changing the coordinate linear and non-linear laws - Tuleuova, R.U. (Bulletin of the Karaganda University. Mathematics Series, 2016)
Many elements of the constructions at the same time experiencing the eﬀects of temperature, heat flow, heat exchange and external mechanical forces diﬀerent amplitude characteristics. At our impacts of rod elements of constructions cannot sustain that leads to disruption of the entire structure. This question is is highly relevant. This work consists in constructing universal computing algorithm based on the application of the finite element method. Essence of the given method consists in sampling non - linear finite element study design. Determined by the law of the temperature distribution on the volume of construction, which minimizes on key values moving, get a field of elastic, temperature and thermal stress of the components of strain and stress.